2016
DOI: 10.1186/s12014-016-9109-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of serum biomarkers in Duchenne muscular dystrophy

Abstract: Assessments of disease progression and response to therapies in Duchenne muscular dystrophy (DMD) patients remain challenging. Current DMD patient assessments include complex physical tests and invasive procedures such as muscle biopsies, which are not suitable for young children. Defining alternative, less invasive and objective outcome measures to assess disease progression and response to therapy will aid drug development and clinical trials in DMD. In this review we highlight advances in development of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 57 publications
3
58
0
Order By: Relevance
“…The extent of disruption of distinct components of the cytoskeleton/sarcomere may be unequal, as suggested by our finding that the expression of titin was disrupted by lengthening contractions whereas that of desmin, nebulin, and α-actinin was unperturbed. Our data are consistent with two other reports describing abnormal titin staining and reduced passive tension in WT muscle after lengthening contractions (31,34), as well as with the fact that titin fragmentation is detected in serum and urine, in dystrophindeficient mice as well as Duchenne muscular dystrophy patients (54)(55)(56). Disruption of the DGC is accompanied by compromised lateral force transmission (31,34).…”
Section: Discussionsupporting
confidence: 81%
“…The extent of disruption of distinct components of the cytoskeleton/sarcomere may be unequal, as suggested by our finding that the expression of titin was disrupted by lengthening contractions whereas that of desmin, nebulin, and α-actinin was unperturbed. Our data are consistent with two other reports describing abnormal titin staining and reduced passive tension in WT muscle after lengthening contractions (31,34), as well as with the fact that titin fragmentation is detected in serum and urine, in dystrophindeficient mice as well as Duchenne muscular dystrophy patients (54)(55)(56). Disruption of the DGC is accompanied by compromised lateral force transmission (31,34).…”
Section: Discussionsupporting
confidence: 81%
“…A recent study has shown that circulating miRNAs are found to be elevated in serum of patients with Duchenne and Becker muscular dystrophies. The level of the identified miRNAs decreased after exon skipping therapy and restoration of dystrophin protein [16]. …”
Section: Genomics and Transcriptomicsmentioning
confidence: 99%
“…Blood fluid samples are simple to obtain and provide insight into the circulating protein in the entire body in normal as pathological conditions 49 . Initially, serological level of creatine kinase (CK) was used to screen for DMD in newborns 50,51 .…”
mentioning
confidence: 99%